Penerapan kecerdasan intelektual, emosional, dan spiritual untuk menekan perilaku agresif mahasiswa - Fitriah, Wardatul (Maliki Interdisciplinary Journal, 2025)
The rise of aggressive behavior among university students has become a serious concern, requiring a comprehensive approach to character development. This study aims to examine how intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) influence student aggression. The results show that all three types of intelligence jointly affect aggression levels, with spiritual intelligence having the strongest influence in reducing aggressive behavior. These findings highlight the importance of higher education institutions in not only focusing on academic achievement but also fostering students’ emotional and spiritual growth to shape better character. Thus, character development programs in higher education should be designed holistically, encompassing intellectual, emotional, and spiritual intelligence. Learning strategies that integrate reflective activities, self-control training, and social and religious activities can help students understand themselves, respect others, and channel their energy positively. This approach not only suppresses aggressive behavior but also equips students with social and moral skills essential for professional and community life. Furthermore, the results of this study emphasize the need for collaboration between lecturers, counselors, and student organizations in designing interventions that are sustainable and relevant to student needs.